2013
DOI: 10.1111/echo.12329
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Electromechanical Interval May Predict Cardioembolic Stroke in Apparently Low Risk Elderly Patients with Paroxysmal Atrial Fibrillation

Abstract: As compared with echocardiographic parameters of LA size and LA function, AEMI appears to be more useful for identifying PAF patients. AEMI may enable to detect high risk PAF patients, especially those categorized into low risk by CHADS2 score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…in their study detected that lengthened PA‐PDI time may be an independent predictor of stroke and could increase the predictive power of CHA2DS2‐VASc score to predict the risk of stroke when combined with CHA2DS2‐VASc score. Hoshi et al . demonstrated a significantly lengthened AEMD times in patients with high CHA2DS2‐VASc scores in their study and they detected lengthened AEMD times in patients with a history of cardioembolic stroke compared to the patients with no such history.…”
Section: Discussionmentioning
confidence: 77%
“…in their study detected that lengthened PA‐PDI time may be an independent predictor of stroke and could increase the predictive power of CHA2DS2‐VASc score to predict the risk of stroke when combined with CHA2DS2‐VASc score. Hoshi et al . demonstrated a significantly lengthened AEMD times in patients with high CHA2DS2‐VASc scores in their study and they detected lengthened AEMD times in patients with a history of cardioembolic stroke compared to the patients with no such history.…”
Section: Discussionmentioning
confidence: 77%
“…Hoshi et al (27) stated that patients with PAF had a larger left atrial volume index and longer interatrial EMD compared with the normal population. When patients with PAF were reassessed according to their history of cardioembolic stroke, age and interatrial EMD were found to be independently related to cardioembolic stroke; however, no association was demonstrated between the left atrial volume index and history of cardioembolic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In 108 PAF patients and 52 healthy controls, Hoshi et al found that prolonged AEMD (81%) was frequently associated with PAF, the percentage of which was greater than LA volume index (53%) and lateral A' (52%) [8]. Results of ours were consistent with, and supportive of, those in these previous studies [7,8]. Among patients with prior ischemic stroke, the clinical background similar to our MRFs patients, AEMD was shown to be prolonged (not as much prolonged as in AF patients) compared with normal controls [13] Potential mechanisms of prolonged AEMD in AF Longer AEMD implies more heterogeneous propagation impulse within the atria compromised by fatty replacement [17].…”
Section: Previous Studies On Aemd and Afmentioning
confidence: 99%
“…An increased left atrial (LA) volume index is also known as a strong predictor of AF [3][4][5]. It has been reported that the intra-and interatrial conduction time, that is, the atrial electromechanical delay (AEMD), is an index of reflecting pathological changes of the atria [6][7][8][9][10][11][12][13]. AEMD can be measured not only by invasive electrophysiologic study but also by echocardiographic tissue Doppler imaging (TDI) [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%